Immunological response and markers of cell damage in seropositive horses for Toxoplasma gondii - Do Carmo G.M. (2015)
© 2014 Elsevier Ltd.Toxoplasmosis is an important parasitic disease affecting several species of mammals, but little is known about this disease in horses. This study aimed to investigate the levels of several immunological variables and markers of cell damage in the serum of seropositive horses for Toxoplasma gondii. Sera samples of adult horses from the Santa Catarina State, Brazil used on a previous study were divided into groups according to their antibody levels for T. gondii determined by immunofluorescence assay, i.e. 20 samples from seronegative horses (Group A - control), 20 samples from horses with titers of 1:64 (Group B), 20 samples of horses with titers of 1:256 (Group C), and five samples from horses with titers of 1:1024 (Group D). Positive animals (Groups B, C, and D) had higher levels of immunoglobulins (IgM and IgG), pro-inflammatory cytokines (TNF-α, IFN-γ, IL-1, IL-4, and IL-6) and protein C-reactive protein, as well as lower levels of IL-10 (anti-inflammatory cytokine) when compared to seronegative horses (Group A). The nitric oxide levels were also elevated in seropositive horses. Therefore, we have found humoral and cellular immune responses in seropositive horses, and a correlation between high antibody levels and inflammatory mediators. Markers of cell injury by lipid peroxidation (TBARS) and protein oxidation (AOPP) were elevated in animals seropositives for T. gondii when compared to seronegatives. Therefore, seropositive horses to T. gondii can keep active immune responses against the parasite. As a consequence with chronicity of disease, they show cellular lesions that may lead to tissue damage with the appearance of clinical disease.